Analysis of problems and solutions in teaching fine art classes in general education schools. - M. Giyosiddinova; M. Mo’sajonova (Genius Publishing Group, 2024)
The article discusses the problem of teaching visual arts at school and ways to solve it, and gives recommendations. In particular, problems and solutions in teaching visual arts to elementary school students were discussed and recommendations were given.
Keywords: Topic; idea; artistic style